العلاقة بين تركيز هرمونات قشر الكظر في الوريد المنوي الأيسر وبين معطيات السائل المنوي في حالة القيلة الدوالية اليسرى دراسة لــ 74 حالة في مشفى الأسد الجامعي – اللاذقية - نداف لؤي; عابدين بسام; عمر أديب نزار إحسان (Latakia University Journal -Medical Sciences Series, 2019)
تناول البحث 74 مريض لديهم قيلة دوالية يسرى وخضعوا لعمل جراحي في مشفى الأسد الجامعي خلال عامي2002 – 2003. لقد كان كورتيزول المصل في الوريد المنوي الأيسر بتركيز طبيعي في 40.6%, وبتركيز مرتفع في 27%, وبتركيز منخفض في %32.4. وكان دي هيدروايبي اندروستيرون (DHEA-s) المصل في الوريد المنوي الأيسر بتركيز طبيعي في %70.3, وبتركيز منخفض في %29.7, لكنه لم يملك تركيز مرتفع عن الطبيعي. وكان دلتا 4 اندروستين دي اون (d 4-dione) المصل في الوريد المنوي الباطن الأيسر بتركيز طبيعي في %48.7, وبتركيز مرتفع في %51.3, لكنه لم يملك تركيز منخفض عن الطبيعي. لقد ترافق اضطراب تعداد النطاف مع ارتفاع تركيز الــDHEA-s ثم الــ d 4-dione ثم الكورتيزول في الوريد المنوي الأيسر. و ترافق اضطراب شكل النطاف مع ارتفاع تركيز الــDHEA-s ثم الكورتيزول ثم الــd 4-dione في الوريد المنوي الأيسر. و ترافق اضطراب حركة النطاف مع ارتفاع تركيز الــDHEA-s ثم الـ d 4-dione ثم الكورتيزول في الوريد المنوي الأيسر. The research includes 47 patients who have left varicocele and had a surgical operation at AL-Assad University Hospital during 2002 – 2003. The serum cortisol in the left spermatic vein was in normal concentration in 40.6%, in high concentration in 27%, and in low concentration in 32.4%. And the serum dehydroepiandrosterone (DHEA-s) in the left spermatic vein was in normal concentration in 70.3%, in low concentration in 29.7%, but it was not above normal concentration. And the serum delta 4 androstendione (d 4-dione) in the left spermatic vein was in normal concentration in 48.7%, and in high concentration in 51.3%, but it hasn’t a low concentration. The abnormality of sperm count was accompanied with high concentration of DHEA-s then d 4-dione then cortisol in the left spermatic vein. And the abnormality of sperm morphology was accompanied with high concentration of DHEA-s then cortisol then d 4-dione in the left spermatic vein. And the abnormality of sperm motion was accompanied with high concentration of DHEA-s then d 4-dione then cortisol in the left spermatic vein.